Hierarchically ordered crystalline microporous material with long-range mesoporous orderliness with hexagonal symmetry
Through alkali-mediated desilication and supramolecular template technology, a grading orderly zeolite with hexagonal symmetry was prepared, which solved the problems of poor mass transfer ability and coking sensitivity in narrow micropores, achieving more efficient Catalytic performance and stability.
Patent Information
- Application Number
- CN202380051795.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-09
- Filing Date
- 2023-06-28
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to effectively solve the poor mass transfer capability of zeolites in narrow micropores and their coking sensitivity, which limits their potential in different energy economies and the accessibility of internal functional sites.
By adopting alkali-mediated desilication method and combined with supramolecular template technology, a graded orderly zeolite with hexagonal symmetry was prepared to form a clearly defined long-range mesoporous order structure, which improves the diffusion ability and catalytic performance of species .
More effective species diffusion is achieved, catalytic performance and hydrothermal stability are improved, coke formation is reduced, and accessibility of the Brownsted acid site and Lewis acid site is enhanced.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present disclosure relates to hierarchically ordered crystalline microporous materials. Background Art
[0002] Zeolites are microporous aluminosilicate materials with well-defined structures and uniform pore sizes (pores typically up to about 20 Å) that can be measured in nanometers or angstroms (Å). Typically, zeolites include framework atoms such as silicon, aluminum and oxygen arranged as silica and alumina tetrahedra. Zeolites are generally hydrated aluminosilicates that can be prepared or selected to have controlled porosity and other characteristics, and typically contain cations, water and / or other molecules located in a porous network. There are hundreds of natural and synthetic zeolite framework types with a wide range of applications. Many zeolites occur naturally and are widely mined, while a large number of interdependent studies have produced a large number of synthetic zeolites with different structures and compositions. The unique properties of zeolites and the ability to tailor zeolites for specific applications have led to the widespread use of zeolites in industry as catalysts (e.g., catalytic cracking of hydrocarbons or as components in catalytic converters), molecular sieves, adsorbents (e.g., desiccants), ion exchange materials (e.g., water softening) and for the separation of gases. Some types of zeolites can be used in various processes and many other applications in oil refineries. Zeolite pores can form sites for catalytic reactions and can also form channels that selectively exclude other compounds and / or isomers for some compounds and / or isomers. Separately or with the addition of active components, zeolites can also have acidity levels that enhance their effectiveness as catalytic materials or adsorbents. Described below is only one of the hundreds of types of zeolites identified by the International Zeolite Association (IZA). The properties and uses of many of these are well known.
[0003] Zeolite Y (also known as Na-Y zeolite or Y-type faujasite) is a well-known material, which zeolite has ion exchange, catalytic and adsorption properties. Zeolite Y is also a useful starting material for the production of other zeolites such as ultrastable Y-type zeolite (USY). Like typical zeolites, faujasite is synthesized as follows: from alumina and silica sources, dissolved in alkaline aqueous solution and crystallized. Faujasite has a framework designated as FAU by IZA and is formed by a 12-ring structure, which is made of a super cage with a pore opening diameter of about 7.4 angstroms (Å) and a sodalite cage with a pore opening diameter of about 2.3 Å. Faujasite is characterized by a three-dimensional pore structure with pores extending perpendicular to each other in the x, y and z planes. The secondary building units can be located at 4, 6, 6-2, 4-2, 1-4-4 or 6-6. Examples of faujasite zeolites have a silica to alumina ratio (SAR) ranging from about 2 to about 6, with typical unit cell sizes (units a, b, and c) ranging from about 24.25 to 24.85 Å. When the SAR is about 2-3, the faujasite zeolite is typically considered to be type X, and when the SAR is greater than about 3, such as about 3-6, the faujasite zeolite is typically considered to be type Y. Typically, the faujasite zeolite is in the sodium form and can be ion exchanged with ammonium, and the ammonium form can be calcined to convert the zeolite to its proton form.
[0004] While zeolites have great utility in their ability to select between small molecules and different cations, mesoporous solids (pores between about 20 and 500 Å) offer the possibility of applications for species that are up to an order of magnitude larger in size, such as nanoparticles and enzymes. The relatively bulky nature of such species hinders diffusion through the microporous zeolite network, and therefore, larger porous systems are required to effectively perform similar molecular sieving actions on larger species.
[0005] Mesoporous silica is amorphous; however, it is the pores that possess long-range order with a periodically arranged pore structure and uniform pore size on the mesoscale. Mesoporous silica offers high surface area and can be used as a host material to introduce additional functionality for a diverse range of applications such as adsorption, separation, catalysis, drug delivery, and energy conversion and storage.
[0006] An attractive property of ordered structures is that their construction (architecture) can be described with respect to their symmetry. The regular form of a crystal is related to the regular arrangement of the subunits comprising the crystal, and therefore, the symmetry of the crystal is related to the symmetry of the subunits. For example, seven different three-dimensional crystal units are provided in Table 1. Crystal systems can be subdivided according to the symmetry elements (collectively referred to as point groups) present, and are provided in Table 2. For example, 3m infers that there is a mirror plane with a triple axis. For 3 / m (or 6) classes, the mirror plane is perpendicular to the triple axis. In a 2D space with a dimension less than 3D, for example, in a layered system, there are four types of crystal systems: hexagonal, square, rectangular and oblique.
[0007] The well-defined microporous structure of zeolite provides a mixture (amalgam) of important physicochemical functions highly expected in various industrial practices. Their pore channels with molecular sizes embedded with adjustable acid / base sites can geometrically distinguish the entry of guest species and direct shape selectivity conversion. Such remarkable properties uniquely shown by zeolite have proved unprecedented importance in many chemical technologies (including but not limited to oil refining, detergent and effluent elimination), which have profound impacts on global economy and environment. However, zeolite performance is often hindered by the poor mass transfer capacity caused by their configuration diffusion in narrow micropores. Therefore, alleviating inherent mass transfer restrictions is important for exploring the full potential of zeolite in different energy economies, and thus enhancing the accessibility to internal functional sites. Other shortcomings of microporous zeolites as catalysts in some reactions are their sensitivity to coking, which can cause accelerated deactivation and product selectivity of catalysts.
[0008] In this regard, hierarchically ordered zeolites (HOZ) with an ordered mesoporous structure and zeolitized mesopore (mesopore) walls are of great technological importance due to their excellent properties. The HOZ contains layers of different porosities (i.e., mesopores and micropores). Hierarchically ordered zeolites offer advantages over conventional microporous zeolites by, for example, improving diffusion of guest species to active sites, overcoming steric limitations, improving product selectivity, reducing coke formation, improving hydrothermal stability, and improving accessibility of Bronsted and Lewis acid sites; and concomitantly, improved catalytic performance.
[0009] Many synthetic strategies for producing hierarchical zeolites are known and fall into two major categories: bottom-up approaches, including the use of hard and soft templates, and top-down approaches, which typically involve post-synthetic processing. Bottom-up strategies generally involve template techniques used in situ during zeolite crystallization, such as the use of hard templates (carbon sources) or soft templates (surfactants). Top-down strategies generally involve post-synthetic modification of already formed zeolite crystals, for example, by steaming, dealumination (using acids) or desiliconization (using bases). A disadvantage of known processes for producing hierarchically ordered zeolites is that the long-range order of the mesophase in the resulting zeolite is limited or non-existent, and the mesopores can be random in size, position and order.
[0010] Base-mediated desilication provides a direct route to generate mesopores (mesoporosity) in high silica frameworks obtained by steam distillation. (See, for example: Verboekend, D., Milina, M., Mitchell, S. & Perez-Ramirez, J. Hierarchical Zeolites by Desilication: Occurrence and Catalytic Impact of Recrystallization and Restructuring. Crys. Growth Des. 13, 5025-5035 (2013)). In particular, the integration of organic templates during the desilication process has significantly improved crystallinity and mesopores. (See, for example: García-Martínez, J., Johnson, M., Valla, J., Li, K. & Ying,JY Mesostructured Zeolite Y—High Hydrothermal Stability and Superior FCCCatalytic Performance. Catal. Sci. Tech. 2, 987 (2012); Mendoza-Castro, MJ,Serrano, E., Linares, N. & García-Martínez, J. Surfactant-Templated Zeolites:From Thermodynamics to Direct Observation. Adv. Mater. Interfaces 8, 2001388(2020)). However, such post-synthetic modification strategies typically lack control over the dissolution and self-assembly processes, resulting in poorly interconnected mesopores. (See, e.g., Schwieger, W. et al. Hierarchy Concepts: Classification and Preparation Strategies for Zeolite Containing Materials with Hierarchical Porosity. Chem. Soc. Rev. 45, 3353-3376, doi: 10.1039 / c5cs00599j (2016)).
[0011] In view of the existing attempts to produce hierarchically ordered zeolites, there remains a need in the art for hierarchically ordered zeolites. With respect to these and other problems in the art, the present disclosure is directed to providing solutions to compositions of hierarchically ordered zeolites having well-defined long-range mesopore order with hexagonal symmetry. Summary of the invention
[0012] Compositions of matter are provided, which include crystalline microporous materials, such as hierarchically ordered zeolites or zeolite-type materials. These hierarchically ordered crystalline microporous materials have well-defined long-range mesoporous order of hexagonal symmetry, including mesopores having walls of the crystalline microporous material and a large number of mesostructures between the mesopores composed of the crystalline microporous material. The long-range order is defined by the presence of secondary peaks in an X-ray diffraction (XRD) pattern and / or hexagonal symmetry observable by microscopy.
[0013] In some embodiments, a composition of matter comprises a hierarchically ordered crystalline microporous material having a well-defined long-range mesoporous order of hexagonal symmetry, the hierarchically ordered crystalline microporous material comprising mesopores having walls comprised of the crystalline microporous material and a plurality of mesostructures between the mesopores of the crystalline microporous material. At least a portion of the mesopores contain micelles of a supramolecular template shaped to induce mesoporous order of hexagonal symmetry. The supramolecular template has one or more dimensions that are larger than the dimensions of the micropores of the crystalline microporous material to restrict diffusion into the micropores of the crystalline microporous material, wherein the dimensions relate to a head group of the supramolecular template, a tail group of the supramolecular template, or a co-template arrangement that restricts diffusion into the micropores of the crystalline microporous material. In some embodiments, an ionic co-solute is present in the hierarchically ordered crystalline microporous material; in some embodiments, the ionic co-solute comprises In some embodiments, the supramolecular template is characterized by a surfactant packing parameter g in the range of about 0.4-0.6, where g, , where V = the total volume of the surfactant tail of the supramolecular template, a0 = the area of the head group of the supramolecular template, and l = the length of the surfactant tail of the supramolecular template. In some embodiments, the molar ratio of the supramolecular template to the cosolute is in the range of about 0.8-1.3.
[0014] In some embodiments, the hexagonal mesophase has p6m, p6mm, or P63 / mmc symmetry. In some embodiments, the hexagonal mesophase has p6m symmetry and secondary peaks in XRD exist at (11) and / or (20) reflections. In some embodiments, the hexagonal mesophase has p6mm symmetry and long-range order can be observed by microscopic observation of electron beams perpendicular to the mesopores along the
[110] crystal zone axis or parallel to the mesopores along the
[001] crystal zone axis. In some embodiments,
[0015] In some embodiments, the parent crystalline microporous material comprises a zeolite or a zeolite-type material. For example, the parent crystalline microporous material is a zeolite selected from AEI, Zeolites having a framework of BEA, CHA, FAU, MFI, MOR, LTL, LTA and MWW. In some embodiments, the parent crystalline microporous material is a zeolite having a FAU framework.
[0016] In some embodiments, a hydrocracking catalyst is provided, which includes a hierarchically ordered zeolite as described herein, an inorganic oxide component as a binder, and an active metal component. For example, the hierarchically ordered crystalline microporous material accounts for about 0.1-99, 0.1-90, 0.1-80, 0.1-70, 0.1-50, 0.1-40, 2-99, 2-90, 2-80, 2-70, 2-50, 2-40, 20-100, 20-90, 20-80, 20-70, 20-50 or 20-40 weight % of the hydrocracking catalyst. Inorganic oxide component is selected from alumina, silica, titania, silica-alumina, alumina-titania, alumina-zirconia, alumina-boria, phosphorus-alumina, silica-alumina-boria, phosphorus-alumina-boria, phosphorus-alumina-silica, silica-alumina-titania, silica-alumina-zirconia, alumina-zirconia-titania, phosphorus-alumina-zirconia, alumina-zirconia-titania and phosphorus-alumina-titania. In some embodiments, the inorganic oxide component includes alumina. In some embodiments, the zeolite includes FAU zeolite. In some embodiments, the active metal component includes one or more of Mo, W, Co or Ni (oxide or sulfide). The active metal component includes one or more metals selected from the 6th, 7th, 8th, 9th or 10th group of the periodic table IUPAC.
[0017] In some embodiments, a method for hydrocracking a hydrocarbon oil is provided, comprising: hydrocracking a hydrocarbon oil with a hydrocracking catalyst comprising a hierarchically ordered zeolite as described herein. In some embodiments, the hydrocarbon oil comprises a recycle stream obtained from the hydrocracking of VGO, straight run VGO, or pretreated straight run VGO, wherein the selectivity to naphtha is tailored as a function of the hexagonal symmetry mesophase.
[0018] Any combination of the various embodiments and implementations disclosed herein may be used.These and other aspects and features may be understood from the following description of some embodiments together with the accompanying drawings and claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The process of the present disclosure will be described in more detail below and with reference to the accompanying drawings, wherein like reference numerals are used for the same or similar elements.
[0020] Figure 1 and 2 is a schematic overview of the hierarchical order of synthetic pathways through the post-synthetic ensembles described herein.
[0021] Figure 3A -B depicts low-angle and high-angle XRD patterns, Figure 4A The N2 physical adsorption isotherm is depicted, and Figure 4B The DFT pore size distributions of the parent zeolite and the synthetic material from Examples 1A-B are depicted.
[0022] Figure 5A -C is a transmission electron microscope micrograph of the hierarchically ordered zeolite synthesized in Example-1B.
[0023] Fig. 6A -B depicts the low-angle and high-angle XRD patterns of the hierarchically ordered zeolite synthesized in Example 2.
[0024] Fig. 7A -E depicts a TEM micrograph of the hierarchically ordered zeolite synthesized in Example-2.
[0025] Figure 8 Graph of the hydrocracking activity (percent conversion per acid site) and selectivity (naphtha, middle distillate, and heavy distillate) of the synthetic materials and parent zeolites in the Examples herein.
[0026] Fig. 9 CO2 curves from char combustion and thermogravimetric analysis of spent samples from the parent zeolite as well as the synthetic materials in the Examples herein are depicted. DETAILED DESCRIPTION
[0027] Compositions of matter are provided, which include hierarchically ordered crystalline microporous materials ("CMMs"). These hierarchically ordered crystalline microporous materials ("HOCMMs") have a well-defined long-range mesoporous order of hexagonal symmetry, and the hierarchically ordered crystalline microporous materials include mesopores with walls of crystalline microporous materials and a large number of mesostructures between the mesopores of the CMMs. The long-range order is defined by the presence of secondary peaks in an X-ray diffraction (XRD) pattern and / or hexagonal symmetry observable by microscopy. In some embodiments, for example, before calcining the synthesized HOCMMs, at least a portion of the mesopores contain micelles of a supramolecular template shaped to induce mesoporous order of hexagonal symmetry, and wherein the supramolecular template has one or more dimensions larger than the dimensions of the micropores of the crystalline microporous material to limit diffusion into the micropores of the crystalline microporous material. The dimensions are related to the head groups of the supramolecular template, the tail groups of the supramolecular template, or the co-template arrangement that limits diffusion into the micropores of the CMMs. HOCMMs are synthesized using base-mediated recombination by dissolving the parent CMM to the level of structural building blocks of the oligomers of the parent CMM, and minimizing or avoiding amorphization / structural collapse. CMM dissolution and self-assembly are fully controlled to produce HOCMMs with mesoporous order of hexagonal symmetry according to the methods herein, including embodiments using ionic co-solutes. Methods for preparing compositions including those disclosed herein are disclosed in co-pending and co-owned U.S. patent application serial number 17 / 857,671 filed on July 5, 2022 and U.S. patent application serial number 18 / 151,782 filed on January 9, 2023, both of which are entitled "Methods for Synthesis of Hierarchically Ordered Crystalline Microporous Materials with Long-range Mesoporous Ordered," and both are incorporated herein by reference.
[0028] In some embodiments of reorganization to produce the material compositions herein: the rate and extent of CMM dissolution are controlled by using urea as an in situ base and controlling urea hydrolysis by adjusting the hydrothermal temperature and fine-tuning the pH of the solution; during the initial stage of dissolution, the extent of dissolution into smaller oligomers is controlled by surfactant-CMM interactions, whereby the influence of ion-specific interactions (i.e., the anionic Hofmeister effect (AHE)) on supramolecular self-assembly guides the formation of a hierarchically ordered structure with hexagonal mesopore symmetry; in some embodiments, the hierarchically ordered structure has hexagonal P6mm mesopore symmetry.
[0029] According to one embodiment of the method for producing the composition of matter herein, the parent CMM forms an aqueous suspension with an alkaline agent and a supramolecular template agent. In another embodiment, the aqueous suspension includes an ionic cosolute as an additional anion, which is separated from the anion paired with the cation of the supramolecular template. The system is maintained under conditions that induce the parent CMM to be cut into oligomeric units of CMM (having only a small portion of monomer units), and induces the hierarchical reorganization of the oligomeric units into mesostructures. Customize system conditions (including crystallization temperature and time), the selection and concentration of supramolecular templates, and the selection and concentration of alkaline agents to control the cutting of parent CMM into oligomeric units and control the shape reorganization of those oligomeric units around supramolecular template micelles. Promote the dissolution of the parent CMM to the extent of oligomer formation while minimizing monomer formation, which is controlled by the selection of supramolecular templates, alkaline agents, optional ionic cosolutes, and hydrothermal conditions (including temperature and time). In some embodiments, a substantial portion, a significant portion, or a major portion of the parent CMM is cleaved into oligomeric units, with any remaining portion being in the form of monomeric units or atomic constituents of the CMM. In some embodiments, the size of the oligomeric unit corresponds approximately to the wall thickness of the synthesized mesoporous structure HOCMM. In some embodiments, the interfacial curvature of the micelles and oligomeric units under recombination is adjusted to the desired mesostructure and mesoporosity with the aid of optional ionic cosolutes and the Hoffman effect.
[0030] Under effective crystallization conditions and time, and using effective types of supramolecular templates and alkaline agents in effective relative concentrations, hierarchical ordering occurs through post-synthetic assemblies: the parent CMM is cleaved into oligomeric CMM units, which are rearranged around the shaped micelles formed by the supramolecular template. Hierarchically ordered CMMs with well-defined long-range mesoporous order are formed by a supramolecular template method using surfactant micelles. The mesopore walls are characterized by the parent CMM. Effective supramolecular templates include those supramolecular templates that have one or more properties of forming pores, channels and / or cavities of a size that blocks all, a substantial portion, a significant portion or a major portion of the supramolecular template molecules from entering the parent CMM. These methods disclosed herein achieve base-mediated cleavage of CMM crystals into oligomeric components in the presence of supramolecular templates of the types / characteristics disclosed herein, followed by reorganization of the supramolecular templates around well-defined micelles into hierarchically ordered structures with well-defined long-range mesoporous order of 2D-hexagonal symmetry.
[0031] The curvature or shape of the micelle results in a final 2D-hexagonal mesophase symmetry. The formation of micelles by supramolecular template molecules depends on factors such as supramolecular template type, supramolecular template concentration, presence or absence of ionic cosolutes, CMM type, crystallization temperature, type of alkaline reagent, concentration of alkaline reagent, pH level of the system, and / or presence or absence of other reagents. Typically, at low concentrations, supramolecular templates exist as discrete entities. At higher concentrations, i.e., above the critical micelle concentration (CMC), micelles are formed. Hydrophobic interactions in a system comprising the supramolecular template change the packing shape of the supramolecular template into, for example, spherical, oblate or cylindrical micelles, which can then form thermodynamically stable two-dimensional or three-dimensional liquid crystal phases of ordered mesoscopic structures (see, e.g., Zana, R. (ed.). (2005). Dynamics of Surfactant Self-Assemblies: Micelles, Microemulsions, Vesicles and Lyotropic Phases (1st ed.). CRC Press, Chapter 1 of Figure 1 .4, which shows self-assembly based on surfactant and surfactant packing parameters).
[0032] In some embodiments, the Hofmeister series (HS), ion-specific effect or lyotropic sequence is followed to select supramolecular templates and / or ionic cosolutes to control the curvature or shape of the micelle (e.g., spherical, elliptical, cylindrical or monolayer structure) (see, e.g., Beibei Kang, Huicheng Tang, Zengdian Zhao, and Shasha Song. "Hofmeister Series: Insights of IonSpecificity from Amphiphilic Assembly and Interface Property" ACS Omega 5(2020): 6229-6239). In an embodiment of the method disclosed herein for the synthesis of hierarchically ordered microporous crystalline materials with well-defined long-range mesoporous order, the intermediate phase transition of the hierarchical assembly produces different mesostructures based on the anionic Hofman effect and supramolecular self-assembly. Anions of different sizes and charges have different polarizabilities, charge densities and hydration energies in aqueous solution. When paired with positive supramolecular template head groups, these properties can affect the short-range electrostatic repulsion between head groups and hydration at the micellar interface, thereby changing the area (a0) of the head groups. Such ion-specific interactions can be the driving force for changing the micelle curvature and inducing mesophase transitions. Based on HS ( > > > > > > > ), strongly hydrated ions (left side of HS) increase the micelle curvature, while weakly hydrated ions decrease the micelle curvature. Surfactant packing parameters (V = total volume of the surfactant tail, a0 = area of the head group, l = length of the surfactant tail) can be used to describe these intermediate phase transitions. In embodiments herein, hierarchically ordered structures with well-defined long-range mesoporous order of 2D-hexagonal symmetry are formed by selection of supramolecular templates and ionic cosolutes.
[0033] In the methods disclosed herein for the synthesis of hierarchically ordered CMMs with well-defined long-range mesoporous order, suitable alkaline agents include one or more alkaline compounds to maintain the system at a pH level greater than about 8. In some embodiments, the alkaline agent is provided in an aqueous suspension at a concentration of about 0.1-2.0 M. In some embodiments, the alkaline agent is provided in an aqueous suspension at a concentration of about 0.1-5 wt %. In some embodiments, the alkaline agent includes urea. In some embodiments, the alkaline agent includes ammonia. In some embodiments, the alkaline agent includes ammonium hydroxide. In some embodiments, the alkaline agent includes sodium hydroxide. In some embodiments, the alkaline agent includes an alkali metal hydroxide, including hydroxides of sodium, lithium, potassium, rubidium, or cesium.
[0034] In some embodiments, the alkaline agent is effective to achieve controlled hydrolysis; for example, urea can be used as an alkaline agent, and during the hydrolysis, urea reacts to form ammonium hydroxide. For example, a higher urea concentration can be used in the initial step, and the alkalinity can be maintained by gradual urea hydrolysis. In such an embodiment, the pH increases relatively slowly to a maximum pH as a function of time, which is beneficial to the process, rather than adding a certain amount of another alkaline agent such as ammonium hydroxide to the maximum pH in the initial solution. Unlike conventional bases that act quickly, urea is pH neutral under ambient conditions and can be evenly dispersed throughout the zeolite micropores without affecting them.
[0035] In some embodiments, the alkaline reagent comprises a compound having the general formula An alkylammonium cation, wherein X = 1-4, and R1, R2, R3 and R4 can be the same or different C1-C30 alkyl groups, and wherein [A − ] is a counter anion, which can be , , or In some embodiments, the alkaline agent comprises a quaternary ammonium cation having an alkoxysilyl group, a phosphonium group, an alkyl group having a bulky substituent, or an alkoxy group having a bulky substituent. In some embodiments, the alkylammonium cation used in this regard acts as a base rather than as a surfactant or template.
[0036] In some embodiments using ammonia, ammonium hydroxide or an alkali metal hydroxide, amorphous material is also present in the product along with the crystalline material. In some embodiments, upon calcining the as-made HOCMM, the amount of apparent amorphous material present (e.g., overall broad band at 25° (2θ) in XRD) is reduced, indicating apparent "self-healing" after calcination. In some embodiments, by controlled hydrolysis of urea to ammonium hydroxide, the amount of apparent amorphous material present in HOCMM (e.g., overall broad band at 25° (2θ) in XRD) is reduced when compared to alternative pathways such as NaOH or direct use of ammonium hydroxide.
[0037] In the method disclosed herein for the synthesis of hierarchically ordered CMMs with well-defined long-range mesoporous order, a suitable surfactant is provided as a supramolecular template to assist the reorganization and recrystallization of dissolved components (oligomers) through covalent and / or electrovalent interactions. The supramolecular template is provided in an aqueous suspension at a concentration of about 0.01-0.5 M. In some embodiments, the suitable supramolecular template is provided in an aqueous suspension at a concentration of about 0.5-10 wt %. Suitable supramolecular templates are characterized by restricted diffusion within the microporous channels of the parent CMM, referred to as bulky surfactants or bulky supramolecular templates. The diffusion of supramolecular template molecules into micropore-channels or cavities promotes CMM dissolution. This is minimized in the top-down method disclosed herein for the synthesis of hierarchically ordered CMMs with well-defined long-range mesoporous order, wherein the effective supramolecular template minimizes its diffusion or partial diffusion into the CMM pore channels, cavities or window openings. Such supramolecular templates have a suitable size to block such diffusion. The appropriate size may be based on the size of the head group and / or tail group of the supramolecular template. In some embodiments, the appropriate size may be based on a co-template having one or more components with appropriate head and / or tail groups, or a template system arranged in such a way as to minimize or prevent diffusion into the CMM pore channels, cavities or window openings. By minimizing the diffusion of the template into the CMM pore channels, the dissolution of the CMM into oligomers and the overall reorganization and assembly of the hierarchically ordered CMMs with well-defined long-range mesoporous order disclosed herein are promoted. In some embodiments, the supramolecular template is a template in which at least a substantial portion, a significant portion or a major portion of the surfactant does not enter the pores and / or channels of the CMM. For example, compared to quaternary ammonium surfactants including hexadecyltrimethylammonium bromide (CTAB) (~0.25 nm) without such bulky groups, organosilanes (~0.7 nm) are relatively large. In some embodiments, the supramolecular template contains long-chain linear groups (>~0.6 nm). In some embodiments, the supramolecular template contains aromatic or aromatic derivative groups (>~0.6 nm). In some embodiments, the supramolecular template contains one or more bulky groups having dimensions based on modeling the molecular size as a cuboid with dimensions A, B, and C using the van der Waals radii of each atom, wherein one or more, two or more, or all three of the dimensions A, B, and C are sufficiently close in size, or sufficiently large in size, to restrict diffusion into the micropores of the selected parent CMM.
[0038] In some embodiments, the effective surfactant as a supramolecular template contains at least one part as a head group or a tail group, and the part is selected from an organosilane, a hydroxysilyl group, an alkoxysilyl group, an aromatic compound (aromatic), a branched alkyl group, a sulfonate group, a carboxylate group, a phosphate group, and a combination including one of the foregoing parts. In some embodiments, the effective supramolecular template is an organosilane containing at least one hydroxysilyl group as a head group part. In some embodiments, the effective supramolecular template is an organosilane containing at least one hydroxysilyl group as a tail group part. In some embodiments, the effective supramolecular template is an organosilane containing at least one alkoxysilyl group as a head group part. In some embodiments, the effective supramolecular template is an organosilane containing at least one alkoxysilyl group as a tail group part. In some embodiments, the effective supramolecular template contains at least one aromatic compound as a head group part. In some embodiments, the effective supramolecular template contains at least one aromatic compound as a tail group part. In some embodiments, the effective supramolecular template contains at least one branched alkyl group as a head group part. In some embodiments, the effective supramolecular template contains at least one branched alkyl group as a tail group part. In some embodiments, the effective supramolecular template contains at least one sulfonate as a head group portion. In some embodiments, the effective supramolecular template contains at least one sulfonate as a tail group portion. In some embodiments, the effective supramolecular template contains at least one carboxylate as a head group portion. In some embodiments, the effective supramolecular template contains at least one carboxylate as a tail group portion. In some embodiments, the effective supramolecular template contains at least one phosphate as a head group portion. In some embodiments, the effective supramolecular template contains at least one phosphate as a tail group portion. These portions are characterized by one or more dimensions that limit diffusion into the pores of the parent CMM. In some embodiments, where the CMM is characterized by pores of various sizes, the selected portions are characterized by one or more dimensions that limit diffusion into the largest pores of the parent CMM.
[0039] In some embodiments, the effective supramolecular template contains at least one cationic part. In some embodiments, the effective supramolecular template contains at least one cationic part selected from a quaternary ammonium part and a phosphonium part. In some embodiments, the effective supramolecular template contains at least one quaternary ammonium group having a terminal alkyl group having 6-24 carbon atoms. In some embodiments, the effective supramolecular template contains two quaternary ammonium groups, wherein the alkyl group bridging the quaternary ammonium group contains 1-10 carbon atoms. In some embodiments, the effective supramolecular template contains at least one quaternary ammonium group and at least one constituent group - the head group part as described above. In some embodiments, the effective supramolecular template contains at least one quaternary ammonium group and at least one constituent group - the tail group part as described above. In some embodiments, the effective supramolecular template contains at least one quaternary ammonium group, at least one constituent group - the head group part as described above, and an alkyl group containing 1-10 carbon atoms bridging at least one of the quaternary ammonium groups and at least one of the head groups. In some embodiments, an effective supramolecular template contains at least one quaternary ammonium group, at least one constituent group - a tail group portion as described above, and an alkyl group containing 1-10 carbon atoms bridging at least one of the quaternary ammonium groups and at least one of the tail groups.
[0040] In some embodiments, the effective supramolecular template comprises a quaternary ammonium compound and a constituent group comprising one or more bulky organosilane or alkoxysilyl substituents. In some embodiments, the effective supramolecular template comprises a quaternary ammonium compound and a constituent group comprising one or more long-chain organosilane or alkoxysilyl substituents. In some embodiments, the effective supramolecular template cation comprises dimethyloctadecyl (3-trimethoxysilyl-propyl)-ammonium or a derivative of dimethyloctadecyl (3-trimethoxysilyl-propyl)-ammonium. In some embodiments, the effective supramolecular template cation comprises dimethylhexadecyl (3-trimethoxysilyl-propyl)-ammonium or a derivative of dimethylhexadecyl (3-trimethoxysilyl-propyl)-ammonium. In some embodiments, effective supramolecular template cations include bisacyloxy amphiphilic organosilanes such as [2,3-bis(dodecanoyloxy)-propyl](3-(trimethoxysilyl)propyl)-dimethylammonium or derivatives of [2,3-bis(dodecanoyloxy)-propyl](3-(trimethoxysilyl)propyl)-dimethylammonium.
[0041] In some embodiments, an effective supramolecular template comprises a quaternary phosphonium compound and a constituent group comprising one or more bulky aromatic substituents. In some embodiments, an effective supramolecular template comprises a quaternary phosphonium compound and a constituent group comprising one or more bulky alkoxysilyl or organosilane substituents.
[0042] In some embodiments, the effective supramolecular template contains a tail group portion selected from the following: an aromatic group containing 6-50, 6-25, 10-50 or 10-25 carbon atoms, an alkyl group containing 1-50, 1-25, 5-50, 5-25, 10-50 or 10-25 carbon atoms, an aryl group containing 1-50, 1-25, 5-50, 5-25, 10-50 or 10-25 carbon atoms, or a combination of aromatic and alkyl groups with up to 50 carbon atoms. In some embodiments, the effective supramolecular template contains a head group moiety selected from the group consisting of an aromatic group containing 6-50, 6-25, 10-50, or 10-25 carbon atoms, an alkyl group containing 1-50, 1-25, 5-50, 5-25, 10-50, or 10-25 carbon atoms, an aryl group containing 1-50, 1-25, 5-50, 5-25, 10-50, or 10-25 carbon atoms, or a combination of aromatic and alkyl groups having up to 50 carbon atoms. In some embodiments, the effective supramolecular template contains a co-templating agent selected from the group consisting of quaternary ammonium compounds (including, for example, quaternary alkylammonium cationic species) and quaternary phosphonium compounds.
[0043] In some embodiments, the effective supramolecular template includes (a) at least one of the following: an aromatic quaternary ammonium compound, a branched alkyl chain quaternary ammonium compound, an alkylbenzene sulfonate (salt), an alkylbenzene phosphonate (salt), an alkylbenzene carboxylate (salt), or a substituted phosphonium cation; and (b1) and as a head group, a constituent group including at least one of an organosilane, a hydroxysilyl group, an alkoxysilyl group, an aromatic compound, a branched alkyl group, a sulfonate group, a carboxylate group, or a phosphate group; or (b2) and as a tail group, a constituent group including at least one of an organosilane, a hydroxysilyl group, an alkoxysilyl group, an aromatic compound, a branched alkyl group, a sulfonate group, a carboxylate group, or a phosphate group. In some embodiments, the effective supramolecular template includes a sulfonate group (a non-limiting example is sulfonated bis(2-hydroxy-5-dodecylphenyl)methane (SBHDM)). In some embodiments, the effective supramolecular template includes a carboxylate group (a non-limiting example is sodium 4-(octyloxy)benzoate). In some embodiments, effective supramolecular templates include phosphonate groups (a non-limiting example is tetradecyl (1,4-phenyl) diphosphonate). In some embodiments, effective supramolecular templates include aromatic groups (a non-limiting example is benzyl hexadecyl dimethyl ammonium chloride). In some embodiments, effective supramolecular templates include aliphatic groups (a non-limiting example is tetraoctyl ammonium chloride).
[0044] The supramolecular template is provided as a cation / anion pair. In some embodiments, the cation of the supramolecular template is as described above, and is selected from, for example, , , , and In some embodiments, the cation of the supramolecular template is as described above, and the anion, for example , or Pairing. In some embodiments, the effective supramolecular template includes dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride (commonly abbreviated as "TPOAC") or a derivative of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride. In some embodiments, the effective supramolecular template includes dimethylhexadecyl[3-(trimethoxysilyl)propyl]ammonium chloride or a derivative of dimethylhexadecyl[3-(trimethoxysilyl)propyl]ammonium chloride. In some embodiments, the effective supramolecular template includes [2,3-bis(dodecanoyloxy)-propyl](3-(trimethoxysilyl)propyl)-dimethylammonium iodide or a derivative of [2,3-bis(dodecanoyloxy)-propyl](3-(trimethoxysilyl)propyl)-dimethylammonium iodide.
[0045] In some embodiments, the system includes an effective amount of an ionic cosolute (i.e., in addition to the anion paired with the supramolecular template). In some embodiments where an ionic cosolute is used, it is provided at a concentration of about 0.01-0.5 M in the aqueous suspension. In some embodiments where an ionic cosolute is used, it is provided at a concentration of about 0.01-5% by weight in the aqueous suspension. In some embodiments, the ionic cosolute is selected from , , , , , , , , , , and (citrate). In some embodiments, the ionic cosolute is selected based on the Hofmann series / lyotropic series to control the curvature / shape of the micelle to produce the desired hexagonal mesophase symmetry. In some embodiments, sulfate ( ) is an ionic co-solute selected based on the Hofmann series / lyotropic ion series to control the curvature / shape of the micelles to produce a hierarchically ordered CMM with well-defined long-range mesoporous order, which has hexagonal mesophase symmetry; in some embodiments using sulfate as the ionic co-solute, a sulfate salt such as ammonium sulfate or a metal sulfate is used, wherein the metal may be an alkali metal, an alkaline earth metal, a transition metal, a noble metal, or a rare earth metal.
[0046] The present disclosure is applicable to various types of CMMs as matrix materials, including zeolites or zeolite-type materials. In some embodiments, the matrix CMM exhibits good crystallinity and Al distribution to obtain high quality HOCMMs while minimizing complex phases and / or impurities.
[0047] The CMM system is designed to be used in the field of cleaning and maintenance. Read more: ABW, ACO, AEI, AEL, AEN AET、AFG、AFI、AFN、AFO、AFR、AFS、AFT、AFV、AFX、AFY、AHT、ANA、ANO、APC、APD AST、ASV、ATN、ATO、ATS、ATT、ATV、AVE、AVL、AWO、AWW、BCT、BEC、BIK、BOF、B OG、BOZ、BPH、BRE、BSV、CAN、CAS、CDO、CFI、CGF、CGS、CHA、-CHI、-CLO、CON、CS V、CZP、DAC、DDR、DFO、DFT、DOH、DON、EAB、EDI、EEI、EMT、EON、EPI、ERI、ESV、 ETL、ETR、ETV、EUO、EWO、EWS、EZT、FAR、FAU、FER、FRA、GIS、GIU、GME、GON、GOO HEU、IFO、IFR、-IFT、-IFU、IFW、IFY、IHW、IMF、IRN、IRR、-IRY、ISV、ITE、IT G、ITH、ITR、ITT、-ITV、ITW、IWR、IWS、IWV、IWW、JBW、JNT、JOZ、JRY、JSN、JSR、 JST、JSW、KFI、LAU、LEV、LIO、-LIT、LOS、LOV、LTA、LTF、LTJ、LTL、LTN、MAR、M AZ、MEI、MEL、MEP、MER、MFI、MFS、MON、MOR、MOZ、MRT、MSE、MSO、MTF、MTN、MTT、 MTW、MVY、MWF、MWW、NAB、NAT、NES、NON、NPO、NPT、NSI、OBW、OFF、OKO、OSI、OS O、OWE、-PAR、PAU、PCR、PHI、PON、POR、POS、PSI、PTO、PTT、PTY、PUN、PWN、PWO、 PWW、RHO、-RON、RRO、RSN、RTE、RTH、RUT、RWR、RWY、SAF、SAO、SAS、SAT、SAV、S BE、SBN、SBS、SBT、SEW、SFE、SFF、SFG、SFH、SFN、SFO、SFS、SFW、SGT、SIV、SOD、 SOF、SOR、SOS、SOV、SSF、SSY、STF、STI、STT、STW、-SVR、SVV、SWY、-SYT、SZR、T ER、THO、TOL、TON、TSC、TUN、UEI、UFI、UOS、UOV、UOZ、USI、UTL、UWY、VET、VFI、VNI, VSV, WEI, -WEN, YFI, YUG, ZON, BEA, CTH, -EWT, -ITN, MRE, PCS, SFV, -SSO, STO, -SVY and For example, some zeolites known to be useful in the petroleum refining industry include, but are not limited to, AEI, BEA, CHA, FAU, MFI, MOR, LTL, LTA or MWW. In some embodiments, the parent zeolite may be a (FAU) framework zeolite comprising USY, for example, when viewed along the
[111] direction, it has a micropore size associated with the 12-membered ring of 7.4 × 7.4 Å. In some embodiments, the parent zeolite may be a (MFI) framework zeolite comprising ZSM-5, for example, when viewed along the
[100] and
[010] directions, it has a micropore size associated with the 10-membered ring of 5.5 × 5.1 Å and 5.6 × 5.3 Å, respectively. In some embodiments, the parent zeolite may be a (MOR) framework zeolite comprising mordenite, for example, when viewed along the
[001] and
[001] directions, it has a micropore size associated with the 12-membered ring and 8-membered ring of 6.5 × 7.0 Å and 2.6 × 5.7 Å, respectively. In some embodiments, the parent zeolite may be ( In some embodiments, the parent zeolite may be a (BEA) framework zeolite, including zeolite beta polymorph A, for example, having micropore sizes associated with the 12-membered ring of 6.6 × 6.7 Å and 5.6 × 5.6 Å when viewed along the
[100] and
[001] directions, respectively. In some embodiments, the parent zeolite may be a (CHA) framework zeolite, including chabazite zeolite, for example, having micropore sizes associated with the 8-membered ring of 3.8 × 3.8 Å when viewed orthogonal to the
[001] direction. In some embodiments, the parent zeolite may be a (LTL) framework zeolite, including Linde L-type zeolite (zeolite L), for example, having micropore sizes associated with the 12-membered ring of 7.1 × 7.1 Å when viewed along the
[001] direction. In some embodiments, the parent zeolite may be a (LTA) framework zeolite, which includes Linde A-type zeolite (zeolite A), for example, when viewed along the
[100] direction, it has a micropore size associated with the 8-membered ring of 4.1 × 4.1 Å. In some embodiments, the parent zeolite may be an (AEI) framework zeolite, for example, when viewed orthogonally to the
[001] direction, it has a micropore size associated with the 8-membered ring of 3.8 × 3.8 Å. In some embodiments, the parent zeolite may be a (MWW) framework zeolite, which includes MCM-22, for example, when viewed "between layers" and "within layers" orthogonally to the
[001] direction, it has a micropore size associated with the 10-membered ring of 4.0 × 5.5 Å and 4.1 × 5.1 Å, respectively.
[0048] In some embodiments, the parent CMM is a zeolitic material, such as aluminophosphate (AlPO), silicon-substituted aluminophosphate (SAPO), or metal-containing aluminophosphate (MAPO). In some embodiments, the parent CMM is a zeolitic siliceous framework material only.
[0049] As described above, embodiments herein include supramolecular templates containing one or more bulky groups having dimensions based on modeling the molecular dimensions as a cuboid having dimensions A, B, and C using the van der Waals radius of each atom, wherein one or more, two or more, or all three of dimensions A, B, and C are sufficiently close in size, or sufficiently large in size, so as to restrict diffusion into the micropores of the CMM. Also as described above with respect to known parameters associated with the pore size of exemplary zeolites, such parameters affect the selection of supramolecular templates. For example, in the examples herein, FAU zeolite was used; when the supramolecular template material was CTAB (~0.25 nm), HOCMM was not achieved; however, when the supramolecular template was an organosilane (~0.7 nm), HOCMM was achieved because these were closer in size to the pore size of the FAU zeolite, and were therefore restricted from entering such pores. Likewise, suitable supramolecular templates are determined based on the selected parent CMM.
[0050] In some embodiments, the parent CMM used in the method is a zeolite herein having a SAR suitable for a particular type of zeolite. Typically, the SAR of the parent zeolite may be in the following ranges: about 2-10000, 2-5000, 2-500, 2-100, 2-80, 5-10000, 5-5000, 5-500, 5-100, 5-80, 10-10000, 10-5000, 10-500, 10-100, 10-80, 50-10000, 50-5000, 50-100, 50-500 or 50-100. In some embodiments, the SAR of the parent zeolite is greater than or equal to 5 or 10 to achieve long-range order. In embodiments with a SAR of less than 10, uniform mesopores and a certain degree of order may be obtained, and amorphous framework material is retained in the product.
[0051] Figure 1 and 2 A schematic overview of the methods for preparing the compositions disclosed herein using a hierarchical ordering via a post-synthetic ensemble synthesis approach, including the overall synthesis mechanism and how AHE affects the g value to change the micelle curvature and induce the mesophase transition. Figure 1 and 2 The CMM schematically depicted in is a FAU zeolite, but it is understood that other CMMs may be used as parent CMMs to form the compositions herein via a post-synthesis assembly synthesis approach.
[0052] The method includes base-mediated dissolution / cleavage of the parent CMM into oligomeric components, and reorganization into hierarchically ordered mesostructures by supramolecular templating and, in some embodiments, by the Hoffman effect. The parent CMM 10 is provided in a crystalline form. An effective amount of an alkaline agent and an effective amount of a surfactant for supramolecular templating are added to form an aqueous suspension, and the suspension is maintained under hydrothermal conditions to form oligomeric CMM units 12 of the parent CMM (e.g., oligomeric zeolite units when the parent CMM is a zeolite). The supramolecular template molecules 14 form shaped micelles 16, and the oligomeric CMM units are hierarchically reorganized around the shaped micelles and crystallized into ordered mesostructures HOCMM 18, HOCMM 18 having mesopores 20 with limited symmetry and mesopore walls formed by oligomeric CMM units, thereby retaining the micropores 22 of the inherent (subsurface, potential, underlying) CMM structure of the parent CMM. In some embodiments, the material composition herein is HOCMM 18 containing shaped micelles 16. In some embodiments, the composition of matter herein is HOCMM 18, which removes the surfactant 14 formed into shaped micelles 16, for example, by: a chemical method such as solvent extraction, chemical oxidation, or ionic liquid treatment; or a physical method such as calcination, supercritical CO2, microwave-assisted treatment, ultrasound-assisted treatment, ozone treatment, or plasma technology.
[0053] Different mesophase transitions that produce hierarchical ensembles of different mesostructures can be attributed to the synergistic effect of anionic Hofmann effects (ion-specific interactions) in supramolecular self-assembly. Anions of different sizes and charges have different polarizabilities, charge densities, and hydration energies in aqueous solution. When paired with positive surfactant head groups, these properties can affect the electrostatic repulsion between head groups and the hydration at the micelle interface, thereby changing the area (a0) of the head groups. Such short-range ion-specific interactions can be a significant driving force for changing the micelle curvature and inducing mesophase transitions.
[0054] refer to Figure 2, showing the overall synthesis mechanism, including the effect of AHE on g value and the accompanying schematic diagram of micelle curvature and induced mesophase transition. The molar ratio of surfactant to cosolute (which can be expressed as the molar ratio of surfactant to salt) effectively produces the desired mesoporous structure. The molar ratio of surfactant to cosolute is selected to produce a surfactant filling parameter suitable for inducing the mesophase transition to the desired geometry, thereby inducing a change in the micelle curvature. In some embodiments, sulfate is used as an ionic cosolute, the micelle curvature is represented by a surfactant filling parameter g of about 1 / 2 or about 0.4-0.6 or 0.5, and the resulting HOCMM has a long-range mesoporous order with hexagonal symmetry. For example, in some embodiments, the molar ratio of surfactant to cosolute for the synthesis of HOCMM with long-range mesoporous order with hexagonal symmetry can be in the range of about 0.8-1.3, 0.9-1.3, 0.9-12 or 0.8-1.2. The effect of ion-specific interactions (Hoffman effect) on micelle curvature during self-assembly is clear. Anions of different sizes and charges have different polarizabilities, charge densities, and hydration energies in aqueous solution. When paired with positive surfactant head groups, these properties can affect the electrostatic repulsion between head groups and the hydration at the micelle interface, thereby changing the area (a0) of the head groups. Such short-range ion-specific interactions can be a significant driving force for changing the micelle curvature and inducing mesophase transitions. Based on the Hofmann series ( > > > > > > > ), strongly hydrated ions (left side of the series) can increase the micelle curvature, while weakly hydrated ions can reduce the micelle curvature. Although not wishing to be bound by theory, the effect of co-solutes such as salts in the mesophase order can be attributed to their charge balancing effect; in surfactant self-assembly, high density of surfactant molecules are tightly packed into micelles due to hydrophobic effects; as a result, the electrostatic repulsion of the charged head groups should be minimized by counter anions to induce easy aggregation; therefore, although the concentration of the poly(anionic) zeolite component is gradually changed, the auxiliary counter anions play a role in stabilizing the micelles.
[0055] An effective amount of solvent is used in this process. In some embodiments, the solvent is water. In some embodiments, in the presence of a co-solvent selected from a polar solvent, a non-polar solvent, and a pore swelling agent (e.g., 1,3,5-trimethylbenzene), the solvent is water. In some embodiments, in the absence of water, the solvent is selected from a polar solvent, a non-polar solvent, and a pore swelling agent (e.g., 1,3,5-trimethylbenzene). In some embodiments, before heating, the mixture components are added to the reaction vessel together with water. Typically, water allows sufficient mixing to achieve a more uniform distribution of the suspension components, which ultimately produces a more desirable product because each crystal is more closely matched to the next crystal in nature. Inadequate mixing may result in undesirable products or a lower degree of long-range order about the amorphous phase.
[0056] The suspension components are combined in any suitable order and mixed thoroughly to form a uniform distribution of the suspension components. The suspension can be maintained in an autoclave under autogenous pressure (either from the components or from the components plus a gas purge added to the container prior to heating), or in another suitable container, under agitation, such as by stirring, tumbling and / or shaking. The mixing of the suspension components is carried out at about 20-60° C., 20-50° C., or 20-40° C.
[0057] The steps of cleavage and reassembly occur during the hydrothermal treatment to form a solid (product, HOCMM with well-defined long-range mesoporous order of 2D-hexagonal symmetry) suspended in a supernatant (mother liquor). The hydrothermal treatment is performed for a period of about 4-168, 12-168, 24-168, 4-96, 12-96 or 24-96 hours; at a temperature of about 70-250, 70-210, 70-180, 70-160, 70-150, 90-250, 90-210, 90-180, 90-160, 90-150, 110-250, 110-210, 110-180, 110-160 or 110-150°C; and at a pressure of about atmospheric pressure to autogenous pressure. In some embodiments, the hydrothermal treatment occurs in the same container as the container used for mixing, or the suspension is transferred to another container (e.g., another autoclave or low pressure vessel). In some embodiments, the container for the hydrothermal treatment is static. In some embodiments, the container for the hydrothermal treatment is under stirring sufficient to suspend the components.
[0058] HOCMM with well-defined long-range mesoporous order of 2D-hexagonal symmetry is the collected product. The solid is collected using known techniques such as centrifugation, decantation, gravity, vacuum filtration, filter press or drum. The collected HOCMM with well-defined long-range mesoporous order of 2D-hexagonal symmetry is dried, for example, at a temperature of about 50-150, 50-120, 80-150 or 80-120° C., at atmospheric pressure or under vacuum conditions, for a time of about 0.5-96, 12-96 or 24-96 hours.
[0059] In some embodiments, the dried HOCMM having a well-defined long-range mesoporous order of 2D-hexagonal symmetry is calcined, for example to remove the supramolecular templates retained in the mesopores and other components from the mesopores and / or the discrete zeolite unit cell micropores. In embodiments where calcination is performed, the conditions for calcination may include a temperature in the range of about 350-650, 350-600, 350-550, 500-650, 500-600, or 500-550° C., atmospheric pressure or under vacuum, and a time period of about 2.5-24, 2.5-12, 5-24, or 5-12 hours. Calcination may occur at a heating rate in the range of about 0.1-10, 0.1-5, 0.1-3, 1-10, 1-5, or 1-3° C. / minute. In some embodiments, calcination may have a first step of ramping to a temperature of about 100-150° C., holding for about 1.5-6 or 1-12 hours (at a ramp rate of about 0.1-5, 0.1-3, 1-5, or 1-3° C. / minute), then ramping to a higher temperature with a final hold time in the range of about 1.5-6 or 1-12 hours.
[0060] In some embodiments, the supernatant remaining after the product is collected from the system is collected, and all or part of it can be reused as all or part of the solution in the subsequent process of the synthesis of a HOCMM or another HOCMM with a well-defined long-range mesoporous order of 2D-hexagonal symmetry. In this embodiment, the collected supernatant used in the subsequent process is referred to as the supernatant from the previous synthesis. In some embodiments, a new synthesis can occur with the supernatant from the previous synthesis together with the parent CMM. In some embodiments, a new synthesis can occur with the supernatant from the previous synthesis and the parent CMM and an additional amount of supplementary alkaline reagent (such as urea). In some embodiments, a new synthesis can occur with the supernatant from the previous synthesis and the parent CMM and an additional amount of supplementary supramolecular template. In some embodiments, a new synthesis can occur with the supernatant from the previous synthesis and the parent CMM and an additional amount of supplementary ionic co-solutes. In some embodiments, a new synthesis may occur using the supernatant from a previous synthesis along with the parent CMM and additional amounts of supplemental alkaline reagent (eg, urea) and / or supplemental supramolecular template and / or optionally supplemental ionic co-solutes.
[0061] The collected compositions of matter as described herein are hierarchically ordered CMMs (e.g., zeolites) with well-defined long-range mesoporous orderliness of 2D-hexagonal symmetry. These are characterized by defined mesoporous channel directions with CMM microporous channels in the walls of the mesostructure. The HOCMMs collected from the synthesis process with well-defined long-range mesoporous orderliness have supramolecular templates as described herein in the mesopores (i.e., before calcining or extracting the supramolecular template). In some embodiments, the HOCMMs collected from the synthesis process with well-defined long-range mesoporous orderliness of 2D-hexagonal symmetry have micelles of supramolecular templates as described herein in the mesopores (i.e., before calcining or extracting the supramolecular template). The collected compositions of matter as described herein retain the structural integrity of the microporous zeolite structure by: controlled cutting of the parent zeolite, followed by controlled reorganization of the zeolite oligomers under controlled micelle curvature to produce HOCMMs with defined mesoporous 2D-hexagonal symmetry.
[0062] This well-defined long-range mesopore is elusive in the field of hierarchically ordered zeolites. Long-range order is defined by secondary peaks associated with the periodic arrangement of mesopores in the x-ray diffraction (XRD) diagram of a given mesophase, and / or by observation in a microscope, as demonstrated in the embodiments herein. These peaks associated with the mesoporous properties of the product are observed at low 2θ angles. The material also exhibits high-angle peaks associated with zeolites and is observed at high 2θ angles. In some embodiments, low-angle peaks refer to those occurring at 2θ angles less than about 6 °.
[0063] In some embodiments herein, the long-range mesoporous order of the HOCMMs produced according to the methods described herein is characterized by a mesopore periodicity that repeats over a length greater than about 50 nm.
[0064] In some embodiments herein, the HOCMMs herein with well-defined long-range mesoporous order of 2D-hexagonal symmetry have a pore size of about 200-1500, 200-1000, 200-900, 400-1500, 400-1000, 400-900, 500-1500, 500-1000, or 500-900 m 2 / g of surface area. In embodiments herein, the HOCMMs herein with a well-defined long-range mesoporous order of 2D-hexagonal symmetry have a mesopore diameter of about 2-50, 2-20, or 2-10 nm. In embodiments herein, the HOCMMs herein with a well-defined long-range mesoporous order of 2D-hexagonal symmetry have a ratio of silica to alumina of about 2.5-1500, 3-1500, 4-1500, 5-1500, 6-1500, 2.5-1000, 3-1000, 4-1000, 5-1000, 6-1000, 2.5-500, 3-500, 4-500, 5-500, 6-500, 2.5-100, 3-100, 4-100, 5-100, or 6-100. In embodiments described herein, the HOCMMs herein with well-defined long-range mesoporous order of 2D-hexagonal symmetry have a total pore volume of about 0.01-1.50, 0.01-1.0, 0.01-0.75, 0.01-0.65, 0.1-1.50, 0.1-1.0, 0.1-0.75, 0.1-0.65, 0.2-1.50, 0.2-1.0, 0.2-0.75, 0.2-0.65, 0.3-1.50, 0.3-1.0, 0.3-0.75, or 0.3-0.65 cc / g.
[0065] In embodiments herein, the product produced by the above method and demonstrated in the examples herein is characterized by a mesophase having hexagonal symmetry. In some embodiments, the product is a 2D-hexagonal ordered mesoporous zeolite. HOCMM with a mesophase having cubic symmetry is characterized by a hexagonal mesoporous channel orientation, wherein the CMM microporous channels are in the walls of the mesostructure. The hexagonal mesophase may have one of p6m, p6mm or p63 / mmc symmetries. In embodiments herein, the hexagonal mesophase has p6mm symmetry, and secondary XRD peaks associated with the periodic arrangement of mesopores are present at both (11) and (20) reflections. In embodiments herein, the hexagonal mesophase has p6mm symmetry, and a high degree of long-range hexagonal p6mm mesophase order can be observed by microscopy, through electron beam observation perpendicular to the holes along the
[110] crystal zone axis and / or parallel to the holes along the
[001] crystal zone axis. In these embodiments, the CMM structure is arranged with hexagonal p6mm symmetry at the mesoscale, wherein the CMM particles (regardless of their atomic level symmetry or structure) are arranged around micelles (at the mesoscale), and thereby the micelles are arranged to exhibit hexagonal symmetry. Thus, HOCMMs having a hexagonal p6mm mesophase include CMMs characterized by atomic level symmetry and possessing micropores inherent to that type of CMM, which are arranged with hexagonal p6mm symmetry at the mesoscale level with mesopores, wherein the walls of the mesopores and the bulk of the mesostructure between the mesopores are characterized by the CMM (e.g., crystalline zeolites). This is produced as described herein by forming oligomers of the intrinsic CMMs and arranging those oligomers around micelles exhibiting hexagonal symmetry at the mesoscale. In one embodiment, a HOCMM is provided that includes an MFI zeolite having an atomic level orthorhombic symmetry arranged at a mesoscale of hexagonal p6mm symmetry, wherein during the synthesis of a hierarchically ordered zeolite from a parent MFI zeolite, oligomers of the parent MFI zeolite form and arrange around micelles that exhibit hexagonal symmetry at the mesoscale. In one embodiment, a HOCMM is provided that includes a CHA zeolite having an atomic level trigonal symmetry arranged at a mesoscale of hexagonal p6mm symmetry, wherein during the synthesis of a hierarchically ordered zeolite from a parent CHA zeolite, oligomers of the parent CHA zeolite form and arrange around micelles that exhibit hexagonal symmetry at the mesoscale. In one embodiment, a HOCMM is provided that includes a BEA zeolite having atomic level tetragonal symmetry arranged at a mesoscale with a hexagonal p6mm symmetry, wherein during the synthesis of hierarchically ordered zeolites from a parent BEA zeolite, oligomers of the parent BEA zeolite are formed and arranged around micelles exhibiting hexagonal symmetry at the mesoscale.In one embodiment, a HOCMM is provided that includes a MWW zeolite having an atomic level hexagonal symmetry arranged at a mesoscale of hexagonal p6mm symmetry, wherein during the synthesis of a hierarchically ordered zeolite from a parent MWW zeolite, oligomers of the parent MWW zeolite form and arrange around micelles that exhibit hexagonal symmetry at the mesoscale. In one embodiment, a HOCMM is provided that includes a FAU zeolite having an atomic level cubic symmetry arranged at a mesoscale of hexagonal p6mm symmetry, wherein during the synthesis of a hierarchically ordered zeolite from a parent FAU zeolite, oligomers of the parent FAU zeolite form and arrange around micelles that exhibit hexagonal symmetry at the mesoscale.
[0066] The HOCMM produced according to the present disclosure is effective as a catalyst or a component of a catalyst in the hydrocracking of hydrocarbon oils. In some embodiments, a method for hydrocracking hydrocarbon oils is provided herein, including hydrocracking hydrocarbon oils with a hydrocracking catalyst, the hydrocracking catalyst comprising a hierarchical ordered zeolite produced according to the present disclosure. In some embodiments, a method for hydrocracking hydrocarbon oils is provided herein, including hydrocracking hydrocarbon oils with a hydrocracking catalyst, the hydrocracking catalyst comprising a hierarchical ordered FAU zeolite produced according to the present disclosure. In some embodiments, a method for hydrocracking hydrocarbon oils is provided herein, including hydrocracking hydrocarbon oils with a hydrocracking catalyst, the hydrocracking catalyst comprising a hierarchical ordered crystalline microporous material, the crystalline microporous material having a well-defined long-range mesoporous order of hexagonal symmetry, including mesopores with walls of crystalline microporous materials and a large number of mesoscopic structures between the mesopores of the crystalline microporous materials.
[0067] The HOCMM according to the present disclosure is effective as a catalyst or a component of a catalyst in the hydrocracking of hydrocarbon oils. HOCMM can be used as a carrier on which one or more active metal components are loaded as a hydrocracking catalyst. The active metal component is loaded, for example, on a surface including the mesopore wall surface, the micropore wall surface, or the mesopore and micropore wall surface; the active metal component is loaded according to a known method, for example, providing an aqueous solution of the active metal component and subjecting the HOCMM as a catalyst support material to impregnation, incipient wetness impregnation and evaporation, or any other suitable method. In some embodiments, the CMM of the HOCMM comprises a zeolite. In some embodiments, the CMM of the HOCMM comprises one or more zeolite types AEI, BEA, CHA, FAU, MFI, MOR, LTL, LTA or MWW. In some embodiments, the CMM of the HOCMM comprises a FAU zeolite.
[0068] The content of HOCMM and active metal components is appropriately determined according to the object. In some embodiments, the hydrocracking catalyst includes HOCMM as a carrier, and an inorganic oxide component, typically as a binder and / or a granulating agent. For example, the carrier particles (before loading one or more hydrocracking active metal components) may contain HOCMM in the following range: about 0.1-99, 0.1-90, 0.1-80, 0.1-70, 0.1-50, 0.1-40, 2-99, 2-90, 2-80, 2-70, 2-50, 2-40, 20-100, 20-90, 20-80, 20-70, 20-50 or 20-40 weight %, wherein the remaining content is an inorganic oxide. In some embodiments, the support particles (before loading one or more hydrocracking active metal components) may contain HOCMM in the following ranges: about 0.1-99, 0.1-90, 0.1-80, 0.1-70, 0.1-50, 0.1-40, 2-99, 2-90, 2-80, 2-70, 2-50, 2-40, 20-100, 20-90, 20-80, 20-70, 20-50 or 20-40 weight percent, with the remainder being inorganic oxides and one or more other zeolite materials.
[0069] As the inorganic oxide component, any material used in hydrocracking or other catalyst compositions in the related art can be used. Examples thereof include alumina, silica, titania, silica-alumina, alumina-titania, alumina-zirconia, alumina-boria, phosphorus-alumina, silica-alumina-boria, phosphorus-alumina-boria, phosphorus-alumina-silica, silica-alumina-titania, silica-alumina-zirconia, alumina-zirconia-titania, phosphorus-alumina-zirconia, alumina-zirconia-titania, and phosphorus-alumina-titania.
[0070] Active metal component can include one or more metals or metal compounds (oxide or sulfide) known in the hydrocracking field, including those selected from the 6th, 7th, 8th, 9th and 10th families of the periodic table IUPAC. In some embodiments, active metal component is one or more of Mo, W, Co or Ni (oxide or sulfide). Other active metal components can be contained in the catalyst at an effective concentration. For example, the total active component content in the hydrocracking catalyst can exist with an amount known in the relevant art, such as about 0.01-40, 0.1-40, 1-40, 2-40, 5-40, 0.01-30, 0.1-30, 1-30, 2-30, 5-30, 0.01-20, 0.1-20, 1-20, 2-20 or 5-20 W % in terms of metal, oxide or sulfide. In some embodiments, active metal component uses oxide solution loading, and before use, the hydrocracking catalyst is sulfurized.
[0071] In some embodiments, a method for hydrocracking a hydrocarbon oil using a hydrocracking catalyst described herein comprising HOCMM as a component comprises introducing a hydrocarbon oil, for example, having a boiling point in the range of about 370-833, 370-816, 370-650, 375-833, 375-816, or 375-650° C., into a hydrocracking zone in the presence of hydrogen, the hydrocracking zone comprising one or more reactors operated at: a reactor temperature in the range of about 300-500, 300-450, 300-420, 350-500, 350-450, or 350-420° C., a hydrogen partial pressure in the range of about 20-100, 20-70, 20-55, 30-100, 30-70, 30-55, or 40-55 bar, and a heating time of about 0.1-10, 0.2-1.5 h -1 The liquid hourly space velocity ("LHSV", which is the volume flow rate of the liquid feed divided by the volume of the catalyst) in the range of about 500-2,500, 1,000-2,000 normalized cubic meters of hydrogen per cubic meter of oil (Nm 3 / m 3 ). "Hydrocracking zone" means one or more reactors and associated effluent separation devices, and may contain two or more reactors. In some embodiments, the feed is pretreated, or is a recycle stream, within the above boiling point range, wherein the sulfur content is less than 100 ppmw, or 50 ppmw, or 10 ppmw, and the nitrogen content is less than 100 ppmw, or 50 ppmw, or 10 ppmw.
[0072] In the method for hydrocracking hydrocarbon oil according to some embodiments herein, the above-mentioned flow reactor may be a flow reactor selected from a stirred bath type reactor, a boiling bed type reactor, a slurry bath type reactor equipped with baffles, a fixed bed type reactor, a rotating tubular type reactor and a slurry bed type reactor.
[0073] In the method for hydrocracking a hydrocarbon oil according to some embodiments herein, the hydrocarbon oil preferably contains a heavy hydrocarbon oil obtained from (1) crude oil, (2) synthetic crude oil, (3) asphalt, (4) oil sands, (5) shale oil, (6) coal liquid, (7) plastic pyrolysis oil, (8) biomass-derived oil, or (9) Fischer-Tropsch wax.
[0074] In the method for hydrocracking a hydrocarbon oil according to some embodiments herein, the hydrocarbon oil contains a heavy hydrocarbon oil obtained from crude oil, synthetic crude oil, asphalt, oil sands, shell oil, or coal liquid, and the heavy hydrocarbon oil is preferably any one of the following: a) vacuum gas oil (VGO), b) deasphalted oil (DAO) or demetallized oil obtained from a solvent deasphalting process, c) light coker gas oil or heavy coker gas oil obtained from a coking process, d) cycle oil obtained from a fluidized catalytic cracking (FCC) process, e) gas oil obtained from a visbreaking process, or f) a recycle stream obtained from hydrocracking of one or more of (a) to (e). In the method for hydrocracking a hydrocarbon oil according to some embodiments herein, the hydrocarbon oil includes a recycle stream obtained from hydrocracking of VGO. In a method for hydrocracking a hydrocarbon oil using a hydrocracking catalyst described herein including HOCMM as a component according to some embodiments herein, the hydrocarbon oil comprises a recycle stream obtained from the hydrocracking of VGO, straight run VGO, or pretreated straight run VGO, wherein the selectivity for naphtha and / or middle distillates is tailored as a function of the mesophase induced in the HOCMM described herein to allow operational flexibility. In a method for hydrocracking a hydrocarbon oil using a hydrocracking catalyst described herein including HOCMM as a component according to some embodiments herein, the hydrocarbon oil comprises a recycle stream obtained from the hydrocracking of VGO, straight run VGO, or pretreated straight run VGO, wherein the selectivity for naphtha and / or middle distillates is tailored as a function of the mesophase induced in the HOCMM described herein to allow operational flexibility.
[0075] In a method for hydrocracking a hydrocarbon oil using a hydrocracking catalyst described herein comprising a HOCMM as a component according to some embodiments herein, the hydrocarbon oil comprises a recycle stream obtained from the hydrocracking of VGO, straight run VGO, or pretreated straight run VGO, wherein the selectivity to naphtha is tailored as a function of the hexagonal symmetry mesophase induced in the HOCMM described herein to allow for operational flexibility.
[0076] Example
[0077] The HOCMM produced in the examples herein exhibit a significant degree of well-defined long-range mesoporous order, as given by the low-angle XRD pattern. The parent zeolite used in the examples and comparative examples has a FAU framework, zeolite Y (obtained from Zeolyst International, product name CBV 720), and is referred to herein as zeolite HY-15, with a SiO2 / Al2O3 (SAR) of about 30 (Si / Al atomic ratio of 15). Although the examples are shown with respect to this particular zeolite, the methods herein can be applied to another type of parent CMM from another source and as described herein, whether obtained from a commercial manufacturer or from a separate synthesis process. Thus, the resulting composition of matter has a mesoporous structure with micropores and a CMM structure corresponding to the parent CMM. The solutions were prepared at room temperature (RT) and under stirring at 500 RPM.
[0078] Characterization in this article was performed as follows. Powder x-ray diffraction patterns were obtained using a Bruker D8 twin diffractometer, operated at 40 kV and 40 mA, with Cu Kα radiation (λ=0.154 nm) and a step size of 0.02. N2 physical adsorption measurements were performed using a Micromeritics ASAP 2420 instrument at 77 K. All samples were degassed at 350 °C for 12 h prior to analysis. The specific surface area and pore size distribution were calculated using the Brunauer-Emmett-Teller (BET) and non-local density functional theory (NLDFT) models. The t-plot method was used to calculate the micropore volume. High-resolution transmission electron microscopy (TEM) studies were performed using a FEI-Titan ST electron microscope operated at 300 kV. Scanning electron microscopy (SEM) images were obtained using a Nova Nano HR-SEM 240 microscope operated at 4 kV. The samples were sputter-coated with platinum (Pt) to eliminate charging effects before analysis. The Si / Al ratio was calculated as follows: by solid-state magic angle spinning nuclear magnetic resonance (MAS-NMR) experiments using a BrukerAdvance 400MHz instrument, applying 4 μs radio frequency pulses and a 60 second cycle delay. In contrast, the bulk Si / Al ratio of the zeolite was calculated by inductively coupled plasma-emission spectroscopy (ICP-OES) analysis using a 5100 ICP-OES Agilent instrument. Prior to analysis, the sample was mixed with hydrofluoric acid (HF) and nitric acid (HNO3) and digested at 260°C and 160 bar using an UltraWAVE microwave digestion system (Milestone).
[0079] To acquire electron micrographs for tomography reconstruction, zeolite powder was deposited on Quantifoil 300 mesh TEM grids supporting a 2 nm thick continuous carbon film on a holey carbon membrane. Prior to zeolite deposition, a dilute solution of gold nanoparticles (AuNPs) with a diameter of approximately 5 nm was dispersed on the TEM grid. The AuNPs will be used in the alignment of the tomography tilt series. To protect the specimen from beam-induced damage during the long exposure times required for tomography data acquisition, tomography tilt series were acquired on a Krios G4 ( ) electron microscope at liquid nitrogen temperature. The true temperature of the stage level is about -183 ° C. The tilt series is acquired in energy filtering (EF) mode, using a 30 eV slit to increase the contrast of bright field TEM images. Detection is performed on a Falcon i electron direct detector camera, which runs in electron counting mode with a frame size of 4096 pixels. To keep the total exposure dose low, only sample tracking is performed after each tilt series during data acquisition. Refocusing is performed manually about every 10 images. The angular range is ± 64 °, with a tilt step of 1 °. The tilt series are aligned in the IMOD software using 13 AuNPs as fiducial markers, which are clearly visible at each tilt angle. Before reconstruction, 2 image binnings are performed to increase SNR and reduce calculation time. To enhance the visibility of holes in 3D tomograms, images are filtered using an average background subtraction filter (ABSF) implemented as a script in Digital Micrograph. The SIRT reconstruction algorithm runs 100 iterations and uses a relaxation factor of 1.
[0080] Coke quantification was performed by thermogravimetric-temperature programmed oxidation (TG-TPO / MS) equipped with a mass spectrometer using a Mettler-Toledo TGA instrument. Prior to combustion, a 10 °C min -1 The catalyst sample was heated at a rate of 50 mL min under a N2 flow. -1 ) up to 350°C for 0.5 hour. After cooling to 100°C, the coke was burned in air at 5°C min -1 The heating rate was carried out up to 850°C. At the same time, an OmniStarTM mass spectrometer (MS) was used to analyze the CO2 (m / z = 44) profile from the combustion.
[0081] Example 1A: An amount of 2.4 grams of NH4OH was added to 28.3 grams of water while stirring. Into the solution, an amount of 1.0 grams of dry zeolite HY-15 was dispersed and further stirred for 0.25 hours. Then, an amount of 0.4 grams of CTAB was added and further stirred for 0.5 hours. The resulting solution was further stirred for 1 hour and then hydrothermally treated at 130°C for 24 hours. The resulting solid was filtered, washed with water, and dried at 120°C for 24 hours. The synthesized product was calcined at 550°C in air for 6.0 hours at a heating rate of 60°C / hour to obtain AH-CT (wherein AH refers to ammonium hydroxide, and CT refers to CTAB). The AH-CT synthesized according to this procedure exhibits disordered mesopores and Figures 3A-4B and are characterized in Table 3.
[0082] In an alternative procedure, an amount of 2.0 grams of dry zeolite HY-15 was dispersed in 56.6 grams of water under constant stirring. 0.77 grams of hexadecyltrimethylammonium bromide (CTAB) was added to the solution and further stirred for 0.5 hours. Subsequently, 4.75 grams of an aqueous solution of ammonium hydroxide (30 wt %) was added dropwise to the mixture under stirring. The resulting solution was further stirred for 0.5 hours and then hydrothermally treated at 130°C for 24 hours. The resulting solid was filtered, washed with water and dried at 120°C for 24 hours. The synthesized product was calcined at 550°C in air for 6 hours at a heating rate of 60°C / hour to obtain AH-CT, which exhibited disordered mesopores.
[0083] Example 1B: A procedure for the synthesis of a 2D-hexagonal ordered mesoporous FAU-type zeolite is provided. NH4OH in an amount of 2.4 grams is added to 28.3 grams of water while stirring. A dried zeolite HY-15 in an amount of 1.0 grams is dispersed in the alkaline solution and further stirred for 0.25 hours. Then, a dimethyloctadecyl (3-trimethoxysilyl-propyl)-ammonium chloride (DOAC) in an amount of 1.5 milliliters (42.0 weight % in methanol) is added and further stirred for 0.5 hours. The resulting solution is further stirred for 1 hour and then hydrothermally treated at 130°C for 24 hours. The resulting solid is filtered, washed with water, and dried at 120°C for 24 hours. The synthesized product is calcined in air at 550°C for 6.0 hours at a heating rate of 60°C / hour to obtain AH-TMS (wherein TMS refers to DOAC, dimethyloctadecyl (3-trimethoxysilyl-propyl)-ammonium chloride). The AH-TMS formed according to this procedure exhibits 2D-hexagonal ordered mesoporous symmetry and Figures 3A-4B and are characterized in Table 3.
[0084] In an alternative procedure, an amount of 2.0 g of HY zeolite is dispersed in 56.6 g of water under constant stirring. To the solution is added 3.0 ml of DOAC (42.0 wt % in methanol) and further stirred for 0.5 hour. Subsequently, 4.75 g of an aqueous solution of ammonium hydroxide (30 wt %) is added dropwise to the mixture under stirring. The resulting solution is further stirred for 0.5 hour and then hydrothermally treated at 130°C for 24 hours. The resulting solid is filtered, washed with water and dried at 120°C for 24 hours. The synthesized product is calcined at 550°C in air for 6 hours at a heating rate of 60°C / hour to obtain AH-TMS. The AH-TMS formed according to this procedure possesses 2D-hexagonal ordered mesoporous symmetry (as in Figures 5A-5C (this is clearly seen in the TEM image of the AH-TMS presented in FIG. ).
[0085] Example 2: A procedure for the synthesis of 2D-hexagonal ordered mesoporous FAU-type zeolite using sulfate as an ionic co-solute is provided. An amount of 0.6 grams of urea is added to 10.0 grams of water to form a homogeneous solution. To the solution is added an amount of 1.0 grams of dry zeolite HY-15 and stirred for 0.5 hours. Subsequently, 20 milliliters of water, 0.165 grams of ammonium sulfate ((NH4)2SO4) and 1.5 milliliters of DOAC (42.0 wt % in methanol) are gradually added, and the mixture is further stirred for 2 hours. The resulting solution is hydrothermally treated at 130°C for 72 hours. The resulting solid is filtered, washed with water, and dried at 120°C for 24 hours. The synthesized product is calcined at 550°C in air for 6.0 hours at a heating rate of 60°C / hour to obtain US-TMS (wherein U refers to urea, S refers to sulfate, and TMS refers to DOAC). The US-TMS formed according to this procedure exhibits 2D-hexagonal ordered mesoporous symmetry, and at Figure 6A-6B The TEM images are shown in Fig. 7A -E.
[0086] In an alternative procedure, urea in an amount of 1.2 grams was dissolved in 60.0 grams of water to form a homogeneous solution. To the mixture was added 0.33 g of ammonium sulfate (NH4)2SO4) as an ionic cosolute source and stirred until homogeneous. To the mixture was added 2.0 grams of dry zeolite HY-15 and stirred for 10 minutes. Subsequently, 3.0 milliliters of DOAC (42.0 wt % in methanol) was added. The resulting solution was stirred for 0.5 hours and then hydrothermally treated at 130°C for 72 hours. The resulting solid was filtered, washed with water and dried at 120°C for 24 hours. The synthesized product was calcined at 550°C in air at a heating rate of 60°C / hour for 6 hours to obtain US-TMS (wherein Y refers to zeolite Y, U refers to urea, S refers to sulfate, and TMS refers to dimethyloctadecyl (3-trimethoxysilyl-propyl)-ammonium chloride), which possesses 2D-hexagonal ordered mesoporous symmetry.
[0087] In Example 1B, the product hierarchically ordered zeolite is a 2D-hexagonally ordered mesoporous FAU-type zeolite having mesoporous channels arranged in a hexagonal manner, as observed in the
[100] and
[110] directions, with FAU microporous channels in the walls and a large number of mesostructures between the mesopores. Figure 3A Depicted is the low-angle XRD pattern, Figure 3B Depicted is the high-angle XRD pattern, Figure 4A The N2 physical adsorption isotherm is depicted, and Figure 4B The NLDFT pore size distribution is depicted, where "a" corresponds to HY-15, "b" corresponds to AH-CT, and "c" corresponds to AH-TMS: Figure 5A -C is a transmission electron microscope (TEM) micrograph of AH-TMS, showing hexagonal mesoporous channels in the
[100] and
[110] directions with FAU microporous channels in the walls of the mesostructure, where: Figure 5A TEM micrographs at the 50-nm scale are shown; Figure 5B shows TEM micrographs in the
[100] direction and the
[110] direction at a 20 nm scale, and also depicts the corresponding schematic diagram and unit cell dimensions; and Figure 5C TEM micrographs in the
[100] direction at the 10 nm scale are shown (with an overlay schematic of the intrinsic zeolite structure). The high degree of long-range order results from Figure 3A The low-angle XRD pattern “c” shows Bragg reflections at angles corresponding to the 100, 110, and 210 planes, indicating hexagonal mesoporous symmetry in AH-TMS. In contrast, the low-angle XRD pattern “b” shows disordered mesopores despite a uniform pore size distribution (PSD) from the corresponding N2 physical adsorption isotherm, as shown in Figure 2. Figure 3A and 4AClearly, this is attributed to the inhomogeneous zeolite dissolution and restricted supramolecular self-assembly. The retention of the intrinsic zeolite structure is due to Figure 3B It is clear in Figure 3 that for all samples the high angle XRD patterns are consistent with those of the parent zeolite FAU zeolite. Figure 4A and 4B The N2 physical adsorption isotherms and pore size distribution of the prepared zeolites are depicted. Figure 4A and 4B The high mesopore volume and narrow pore size distribution further support the existence of long-range ordered mesopores.
[0088] The as-prepared and calcined product from Example 2 was Fig. 6A and the calcined product from Example 2 was characterized in Figure 6B In characterization. Fig. 6A The low angle XRD pattern is depicted, and Figure 6B Depicted are high angle XRD patterns where intensity in arbitrary units (au) is plotted against frequency 2θ (°), with the as-prepared pattern shown as dashed lines and the calcined pattern shown as solid lines. The high degree of long-range order of the as-prepared and calcined US-TMS is shown in Figure 1. Fig. 6A The low-angle XRD pattern shows Bragg reflection peaks at 100, 110 and 200, indicating 2D-hexagonal ordered mesoporous symmetry. The retention of the inherent zeolite structure is Figure 6B It is clear that the high angle XRD patterns are consistent with those of the parent zeolite FAU zeolite. Fig. 7A -E presents a TEM micrograph of US-TMS synthesized in the first procedure of Example 2, including: Fig. 7A , with corresponding structural diagrams in the
[100] and
[110] directions at the 20 nm scale; Figure 7B , Fig. 7A A magnified view of a section in the
[100] direction with an inset of the Fast Fourier Transform pattern; a magnified view of a section in the
[110] direction at 50 nm scale Figure 7C , showing the selected area electron diffraction (SAED) in the inset; at 50 nm scale in the
[100] and
[110] directions Fig.7D ; and at 20 nm in the
[100] and
[110] directions Fig. 7E , with a corresponding structure diagram.
[0089] According to the examples herein, hierarchically ordered FAU-type frameworks exhibiting 2D-hexagonal (p6mm) symmetry were prepared for the first time by methodical post-synthetic reorganization.
[0090] Example 3: Evaluation of the catalytic performance of US-TMS 2D-hexagonal ordered mesoporous FAU type zeolite on the low pressure hydrocracking of a recycle stream (second stage feedstock) from a two-stage hydrocracking unit using a fixed bed reactor. The feedstock was a pretreated straight run vacuum gas oil from the first stage hydrocracking unit and therefore contained very low levels of sulfur and nitrogen, 40 ppmw and 17 ppmw, respectively. The composition and properties of the feedstock are listed in Table 4. The catalyst was prepared by mixing a mesoporous FAU type zeolite (30 wt%) with alumina (70 wt%) followed by incipient wet impregnation of nickel (Ni) and molybdenum (Mo) species. In particular, 70 wt% alumina was dispersed in a minimum amount of deionized (DI) water. 30 wt% zeolite was slowly added to the slurry and stirred for 15 minutes. In the next step, the desired amount of (NH4)6Mo7O 24 .4H2O (8.5 wt % Mo), Ni(NO3)2.6H2O (3.0 wt % Ni) and citric acid (7.5 wt %) were added to the slurry of zeolite-alumina and stirred for another 1 h. The mixture thus obtained was dried at 120°C overnight and subsequently calcined at 550°C for 4 h. Dimethyl disulfide (1 mL g -1 The metal oxide supported catalyst obtained in powder form was sulfided in a batch reactor (Parr) at 300°C and 50 bar for 4 hours in the presence of hydrogen (46 mesh) at 40 bar. The catalyst bed was prepared by filling 0.5 g of the sulfide catalyst between two silicon carbide (46 mesh) layers (volume 16 mL), each in a stainless steel cylindrical reactor (SS316; inner diameter 9.1 mm; length 300 mm) with a 20 μm porous plate located at the bottom. The supported catalyst was purged with a H2 / N2 (75:25 volume ratio) gas mixture at a flow rate of 100 mL / h at 450°C and 50 bar for 2 h to remove any moisture. The catalytic studies were carried out at a temperature of 400°C and a pressure of 50 bar with a H2 / oil ratio of 750 Nm 3 / m 3 , and the weight hourly space velocity (WHSV) is 1 h -1 The reaction was carried out for 10 h, and the liquid was separated from the liquid-gas separator and collected regularly after each hour for gas chromatography (GC) analysis. The liquid product was analyzed according to the ASTM D2887 standard test method using an Agilent 6980N GC coupled to simulated distillation (SIMDIS) software.
[0091] The conversion (X) of the feed, the selectivity (S) and the yield (Y) of the desired hydrocarbon mixture naphtha (C4-150°C), kerosene (150-250°C) and gas oil (250-370°C) were calculated from the boiling point distribution curves obtained based on SIMDIS analysis of the literature according to equations (1), (2) and (3), respectively:
[0092]
[0093] in and Corresponds to the fraction (wt%) of material remaining in the feed and product with a boiling point ≥ 370°C.
[0094]
[0095]
[0096] in and Corresponds to the fraction (wt%) of material in the product and feed between boiling points 'x and y'. and Selectivity and yield corresponding to the hydrocarbon fraction between boiling points 'x and y'. The conversion of each acid site is calculated by dividing the conversion obtained by the total number of acid sites quantified by pyridine FTIR spectroscopy at 150°C.
[0097] The acid properties and catalytic performance of the parent zeolite and synthesized US-TMS are shown in Table 5. Despite having a lower concentration of zeolitic acid sites compared to the parent zeolite, the HOCMM synthesized herein demonstrates excellent catalytic performance. Figure 8 Figure 2 is a graph of hydrocracking activity (percent conversion per acid site) and selectivity (naphtha, middle distillate, and heavy distillate) of catalysts formed using parent zeolite and synthetic HOCMM, US-TMS. Compared to the parent zeolite, the synthetic HOCMM herein demonstrates higher conversion and naphtha selectivity.
[0098] The tailoring of the mesophase symmetry and related physicochemical properties induced by achieving a hexagonal symmetric mesophase leads to increased product selectivity, i.e., higher naphtha yield.
[0099] The study of coke properties is also used to determine catalytic stability and lifetime. In this regard, the properties of the coke on the spent catalyst are quantified using a temperature programmed oxidation curve of the CO2 produced by the combustion. Fig. 9Describe the CO curve of the programmed temperature oxidation of the spent catalyst from the upper part and the lower part, wherein mode (a) represents the parent zeolite, and mode (b) represents the hexagonal HOCMM in this article. The catalyst shows two main peaks in the 320-500°C and 500-640°C regions, corresponding to the external coke and internal coke (zeolite micropores) present in the mesopores, respectively. Although it is not desired to be bound by theory, it is expected that the internal coke is the cause of zeolite deactivation, due to its limited combustion during regeneration, especially under low pressure cracking conditions, due to low H / C ratio and poor O accessibility, it tends to form high internal coke, and in this regard, the HOCMM in this article, due to its enhanced diffusion properties, has shown low internal coke deposition (15-20%) compared with the parent (35%) zeolite. In commercial hydrocracking, the zeolite component of the catalyst is critical in providing the refinery with flexibility in its operating mode (ie, middle distillate or naphtha selectivity), and the HOCMM herein can be used to allow the refinery to operate in different operating modes.
[0100] The improved naphtha selectivity indicates improved accessibility of acid sites, and secondary cracking of middle distillate hydrocarbons to naphtha hydrocarbons may occur. The synthesized US-TMS possesses a high B / L acid site ratio and a 2D mesostructure, demonstrating excellent conversion of VGO feedstock and good selectivity to naphtha.
[0101] As used herein, the phrase "major part" about specific composition and / or solution and / or other parameters means at least about 50% and up to 100% of a unit or amount. As used herein, the phrase "significant part" about specific composition and / or solution and / or other parameters means at least about 75% and up to 100% of a unit or amount. As used herein, the phrase "considerable part" about specific composition and / or solution and / or other parameters means at least about 90,95,98 or 99 and up to 100% of a unit or amount. As used herein, the phrase "minor part" about specific composition and / or solution and / or other parameters means at least about 1,2,4 or 10% of a unit or amount, up to about 20,30,40 or 50%.
[0102] It should be understood that the same numbers in the accompanying drawings represent the same elements in multiple drawings, and all parts and / or steps described and shown with reference to the accompanying drawings are not all embodiments or arrangements required. In addition, the terms used in this article are only used to describe the purpose of specific embodiments, and are not intended to limit the present invention. As used in this article, the singular forms "one (kind) (indefinite article a, an)" and "described (the)" are intended to also include plural forms, unless the context clearly states otherwise. It will be further understood that when used in this specification, the terms "include", "comprise", "contain", "have", "contain", "involve", and variations thereof specify the existence of stated features, integers, steps, operations, elements and / or parts, but do not exclude the existence or addition of one or more other features, integers, steps, operations, elements, parts, and / or their sets.
[0103] It should be noted that the use of ordinal terms such as "first", "second", "third", etc. to modify claim elements in the claims does not itself imply any priority, precedence or order of one claim element relative to another claim element, or the temporal order in which the actions of the method are performed, but is merely used as a label to distinguish one claim element with a specific name from another element with the same name (but using ordinal terms) to distinguish the claim elements.
[0104] It is noteworthy that the above drawings and examples are not meant to limit the scope of the present disclosure to a single implementation, because some or all of the other implementations of the elements described or shown by the interchange are also possible. In addition, in the case where some elements of the present disclosure can be partially or completely implemented using known parts, only those parts of such known parts required for understanding the present disclosure are described, and the detailed description of other parts of such known parts is omitted to avoid blurring the present disclosure. In this specification, unless otherwise clearly stated herein, the embodiment showing a single component is not necessarily limited to other implementations including a plurality of identical components, and vice versa. In addition, the applicant does not intend to attribute any term in the specification or claims to uncommon or special meanings, unless clearly stated in this manner. In addition, the present disclosure covers the current and future known equivalents of the known parts mentioned herein by way of illustration.
[0105] The foregoing description of a specific implementation will fully reveal the general nature of the present disclosure so that others can easily modify and / or adjust such specific implementations for various applications without departing from the general concept of the present disclosure by applying the knowledge of technicians in the relevant fields, without excessive experimentation. Therefore, based on the teachings and guidance presented herein, such adjustments and modifications are intended to fall within the meaning and scope of the equivalents of the disclosed implementations. It is understood that the wording or terminology herein is for descriptive and non-limiting purposes, so that the terms or wording of this specification will be interpreted by those skilled in the art according to the teachings and guidance presented herein in combination with the knowledge of technicians in the relevant fields. It should be understood that the dimensions discussed or shown are drawings according to an example, and other dimensions can be used without departing from the present disclosure.
[0106] The above-described subject matter is provided by way of illustration only and should not be construed as limiting. Various modifications and changes may be made to the subject matter described herein without following the example implementations and applications shown and described and without departing from the true spirit and scope of the invention encompassed by the present disclosure, which is defined by a set of recitations in the appended claims and by structures and functions or steps equivalent to those recitations.
[0107]
[0108]
[0109]
[0110]
[0111]
Claims
1. A composition of matter comprising a hierarchically ordered crystalline microporous material having a well-defined long-range mesoporous order of hexagonal symmetry, the hierarchically ordered crystalline microporous material comprising mesopores having walls of the crystalline microporous material and a plurality of mesostructures between the mesopores of the crystalline microporous material, wherein the long-range order is defined by the presence of secondary peaks in an X-ray diffraction (XRD) pattern and / or by hexagonal symmetry observable by microscopy.
2. A composition of matter comprising a hierarchically ordered crystalline microporous material having a well-defined long-range mesoporous order of hexagonal symmetry, the hierarchically ordered crystalline microporous material comprising mesopores having walls of the crystalline microporous material and a plurality of mesostructures between the mesopores of the crystalline microporous material, wherein at least a portion of the mesopores contain micelles of a supramolecular template shaped to induce mesoporous order of hexagonal symmetry, and wherein the supramolecular template has one or more dimensions larger than the dimensions of the micropores of the crystalline microporous material to restrict diffusion into the micropores of the crystalline microporous material, wherein the dimensions relate to head groups of the supramolecular template, tail groups of the supramolecular template, or co-template arrangements that restrict diffusion into the micropores of the crystalline microporous material.
3. The composition of matter of claim 2, further comprising an ionic co-solute.
4. The composition of matter of claim 2 or 3, wherein the supramolecular template is characterized by a surfactant packing parameter g in the range of about 0.4-0.6, wherein: in V = the total volume of the surfactant tails of the supramolecular template, a0 = the area of the head group of the supramolecular template, and l = length of the surfactant tail of the supramolecular template.
5. The composition of matter according to claim 3 or 4, wherein the ionic cosolute comprises .
6. The composition of matter according to any one of claims 3 to 5, wherein the molar ratio of the supramolecular template to the co-solute is in the range of about 0.8 to 1.
3.
7. The composition of matter according to any one of claims 1 to 6, wherein the hexagonal mesophase has p6m, p6mm or P63 / mmc symmetry.
8. The material composition according to any one of claims 1 to 6, wherein the hexagonal mesophase has p6mm symmetry and secondary peaks in XRD exist at (11) and / or (20) reflections.
9. The composition of matter of any one of claims 1 to 6, wherein the hexagonal mesophase has p6mm symmetry and the long-range order can be observed by microscopic observation of an electron beam perpendicular to the mesopores along the [110] crystal zone axis or parallel to the mesopores along the [001] crystal zone axis.
10. The composition of matter of any one of claims 1 to 9, wherein the crystalline microporous material comprises a zeolite or a zeolite-type material.
11. The composition of matter according to any one of claims 1 to 9, wherein the crystalline microporous material is selected from the group consisting of AEI, Framework zeolites of BEA, CHA, FAU, MFI, MOR, LTL, LTA and MWW.
12. The composition of matter of any one of claims 1 to 9, wherein the parent crystalline microporous material is a zeolite having a FAU framework.
13. A hydrocracking catalyst comprising the hierarchically ordered crystalline microporous material according to any one of claims 10, 11 or 12, an inorganic oxide component as a binder, and an active metal component.
14. The hydrocracking catalyst of claim 13, wherein the hierarchically ordered crystalline microporous material comprises about 0.1-99, 0.1-90, 0.1-80, 0.1-70, 0.1-50, 0.1-40, 2-99, 2-90, 2-80, 2-70, 2-50, 2-40, 20-100, 20-90, 20-80, 20-70, 20-50, or 20-40 weight percent of the hydrocracking catalyst.
15. The hydrocracking catalyst according to claim 13 or 14, wherein the inorganic oxide component is selected from the group consisting of alumina, silica, titania, silica-alumina, alumina-titania, alumina-zirconia, alumina-boria, phosphorus-alumina, silica-alumina-boria, phosphorus-alumina-boria, phosphorus-alumina-silica, silica-alumina-titania, silica-alumina-zirconia, alumina-zirconia-titania, phosphorus-alumina-zirconia, alumina-zirconia-titania and phosphorus-alumina-titania.
16. The hydrocracking catalyst according to claim 13 or 14, wherein the inorganic oxide component comprises alumina.
17. The hydrocracking catalyst of claim 16, wherein the crystalline microporous material comprises FAU zeolite.
18. The hydrocracking catalyst according to claim 17, wherein the active metal component comprises one or more of Mo, W, Co or Ni (oxide or sulfide).
19. The hydrocracking catalyst according to any one of claims 13 to 17, wherein the active metal component comprises one or more metals selected from IUPAC Group 6, 7, 8, 9 or 10 of the Periodic Table of Elements.
20. A method for hydrocracking a hydrocarbon oil comprising: Hydrocracking hydrocarbon oil using the hydrocracking catalyst according to any one of claims 13-19.
21. The process of claim 20 wherein the hydrocarbon oil comprises a recycle stream obtained from the hydrocracking of VGO, straight run VGO or pretreated straight run VGO, wherein the selectivity to naphtha is tailored as a function of the hexagonal symmetry mesophase.
Citation Information
Patent Citations
Methods for synthesis of hierarchically ordered crystalline microporous materials with long-range mesoporous order
US20240009660A1
Methods for synthesis of hierarchically ordered crystalline microporous materials with long-range mesoporous order
US20240010662A1